2015
DOI: 10.3390/v7122936
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Improving Potency and Specificity of Reovirus Oncolysis with Next-Generation Reovirus Variants

Abstract: Viruses that specifically replicate in tumor over normal cells offer promising cancer therapies. Oncolytic viruses (OV) not only kill the tumor cells directly; they also promote anti-tumor immunotherapeutic responses. Other major advantages of OVs are that they dose-escalate in tumors and can be genetically engineered to enhance potency and specificity. Unmodified wild type reovirus is a propitious OV currently in phase I–III clinical trials. This review summarizes modifications to reovirus that may improve po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 202 publications
(253 reference statements)
0
28
0
Order By: Relevance
“…The recent development of a plasmid-based reverse genetics system [ 106 ] for reoviruses provided new options for reovirologists to unveil more aspects of reovirus biology as well as for improving the efficacy in oncolytic reovirus therapy. The powerful reovirus reverse genetics system has primarily been used to resolve issues where reovirus segments are involved in apoptosis, assembly or disassembly, cell tropism and pathogenesis in mice [ 59 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Genetic Modification Of Reovirusmentioning
confidence: 99%
“…The recent development of a plasmid-based reverse genetics system [ 106 ] for reoviruses provided new options for reovirologists to unveil more aspects of reovirus biology as well as for improving the efficacy in oncolytic reovirus therapy. The powerful reovirus reverse genetics system has primarily been used to resolve issues where reovirus segments are involved in apoptosis, assembly or disassembly, cell tropism and pathogenesis in mice [ 59 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Genetic Modification Of Reovirusmentioning
confidence: 99%
“…5); although this position is not in direct contact with putative catalytic sites, it is tempting to speculate that it indirectly affects either cap methylation or viral mRNA exit. As mentioned by others (Mohamed et al 2015), it will clearly be of interest to further examine the nature of the 5'-end of the viral mRNAs produced by these The involvement of the λ1 protein in the level of interferon induction came as a surprise finding in the course of this study. It remains to be determined if the protein can repress interferon signaling in T3D S , a property that is lost in T3D K , or if the T3D K protein positively contribute to the interferon induction.…”
Section: Discussionmentioning
confidence: 65%
“…It thus appears to be essential to gain a further understanding of the viral determinants that control induction of the interferon response and the sensitivity of different viral isolates to this response. This could possibly lead to better optimization of viral strains toward oncolytic activity, as many investigators believe to be possible, and as recently reviewed (Mohamed et al, 2015;Kemp et al, 2016). This is especially envisaged since the advent of plasmid-based reverse genetics to manipulate the viral genome (Lemay, 2011;van den Hengel et al, 2013;Stuart et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both reovirus and adenovirus are heavily pursued as oncolytic therapies. We and others have demonstrated that reovirus mutants exhibit differences in their oncolytic activities, and that second-generation reovirus variants may possess improved oncolytic potency17192627. We have found the Capto Core 700 slurry method to be extremely useful for purifying and comparing various natural isolates (Fig.…”
Section: Discussionmentioning
confidence: 99%